China's Naval Operations in the South China Sea Evaluating Legal, Strategic and Military Factors. - Elleman, Bruce (Renaissance Books, 2017)
Here is a history of the South China Sea (SCS) conflict and the stakes for each of the bordering states and China's (PRC) interaction with them. it examines the US's role in the region. It examines the PRC's perception of the SCS, and its strategy to claim the islands and waters, in the context of the strategies of other stake-holding nations.